2018
DOI: 10.1080/10942912.2018.1489413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characterization and antibiotic resistance of enterococci from traditional cheeses in Turkey

Abstract: The aim of the present work is to provide information about Enterococcus strains isolated from traditional Turkish cheese samples in Ankara (Turkey), focusing on their prevalence, phenotypic and genotypic characteristics, and antibiotic resistance. A total of 213 probable enterococcal isolates isolated from 215 samples were identified by phenotypic and genotypic methods. As a result of 16S rDNA sequence analysis, 88 of the 213 enterococci strains were identified as Enterococcus faecium and 125 as Enterococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
3
18
1
2
Order By: Relevance
“…Similar results were obtainedfor different traditional cheese samples, as reported by Yogurtcu and Tuncer (2013) and Bulajić et al (2015). On the other hand, Pesavento et al (2014) and Sanlibaba and Senturk (2018) reported relatively higher ampicillin resistance than penicillin.…”
Section: Antibiotic Suspectibility Patternssupporting
confidence: 88%
See 4 more Smart Citations
“…Similar results were obtainedfor different traditional cheese samples, as reported by Yogurtcu and Tuncer (2013) and Bulajić et al (2015). On the other hand, Pesavento et al (2014) and Sanlibaba and Senturk (2018) reported relatively higher ampicillin resistance than penicillin.…”
Section: Antibiotic Suspectibility Patternssupporting
confidence: 88%
“…Most of the enterococci have intrinsic resistance to nalidixic acid. Similar results were reported by Yuksel et al (2015) and Sanlibaba and Senturk (2018). Conversely, much lower resistance to nalidixic acid (62%) was reported by Furlaneto- Maia et al (2014).…”
Section: Antibiotic Suspectibility Patternssupporting
confidence: 87%
See 3 more Smart Citations